Euro interest rate swap yields: Some ARDL models - Tanweer Akram; Khawaja Abdullah al Mamun (Levy Economics Institute of Bard College, 2024)
This paper examines the dynamics of euro-denominated (EUR) long-term interest rate swap yields. It shows that the short-term interest rate has an economically and statistically significant effect on EUR swap yields of different maturity tenors, after controlling for various key macroeconomic variables. It presents several autoregressive distributive lag (ARDL) models of the dynamics of EUR swap yields. The estimated econometric models of EUR swap yields of different maturity tenors imply that the European Central Bank (ECB) exerts substantial influence on interest rate swap yields, primarily through the effect of its actions on the current short-term interest rate. Examining the case of EUR interest rate swaps, the findings of the paper lend additional credence to John Maynard Keynes's hypothesis concerning the ability of a central bank to influence long-term market interest rates.
Keywords: E43; E50; E60; G10; G12; 330; Euro Swaps; Interest Rate Swaps; Short-Term Interest Rate; Monetary Policy; European Central Bank (ECB); Autoregressive Distributed Lag (ARDL)